Genetic screening of Fabry patients with EcoTILLING and HRM technology - Iemolo Francesco; Francofonte Daniele; Zizzo Carmela; Albeggiani Giuseppe; Nuzzo Domenico; Bono Caterina; Sanzaro Enzo; Duro Giovanni (BMC Research Notes, 2011)
Abstract Background Anderson-Fabry disease (FD) is caused by a deficit of the α-galactosidase A enzyme which leads to the accumulation of complex sphingolipids, especially globotriaosylceramide (Gb3), in all the cells of the body, causing the onset of a multi-systemic disease with poor prognosis in adulthood. In this article, we describe two alternative methods for screening the GLA gene which codes for the α-galactosidase A enzyme in subjects with probable FD in order to test analysis strategies which include or rely on initial pre-screening. Findings We analyzed 740 samples using EcoTILLING, comparing two mismatch-specific endonucleases, CEL I and ENDO-1, while conducting a parallel screening of the same samples using HRM (High Resolution Melting). Afterwards, all samples were subjected to direct sequencing. Overall, we identified 12 different genetic variations: -10C>T, -12G>A, -30G>A, IVS2-76_80del5, D165H, C172Y, IVS4+16A>G, IVS4 +68 A>G, c.718_719delAA, D313Y, IVS6-22C>T, G395A. This was consistent with the high genetic heterogeneity found in FD patients and carriers. All of the mutations were detected by HRM, whereas 17% of the mutations were not found by EcoTILLING. The results obtained by EcoTILLING comparing the CEL I and ENDO-1 endonucleases were perfectly overlapping. Conclusion On the basis of its simplicity, flexibility, repeatability, and sensitivity, we believe that HRM analysis of the GLA gene is a reliable presequencing screening tool. This method can be applied to any genomic feature to identify known and unknown genetic alterations, and it is ideal for conducting screening and population studies.